ANALISIS WACANA KRITIS TERHADAP PERLAWANAN MARGINALISASI PEREMPUAN DALAM ISLAM PADA LAMAN MUBADALAH.ID - Aliftya Amarilisyariningtyas (Kafa`ah: Journal of Gender Studies, 2022)
The 'hijrah' movement in Indonesian society has grown in recent years. This phenomenon is then used to campaign for various matters related to religious issues with various interests. The problem is that these campaigns under the guise of religion are often discriminatory for women. By imposing the logic of the social construction of gender as a 'gifted', people use hijrah to restrict the role of women in public space. Ironically, media industries in Indonesia also provide a space for those campaigns. Regarding this case, few mainstream media have generated counter-discourse. Criticism of this phenomenon is found sporadically in "alternative" media, such as Mubadalah.id. Based on this fact, this research tries to describe how Mubadalah.id raises a discourse against women's marginalization in Islam. By using Norman Fairclough's critical discourse analysis, the researcher analyzed discourse through three levels: text, discourse practice, and sociocultural practice. The results depict that Mubadalah.id represents a form of marginalization as a discourse that is contrary to gender equality in Islam. Mubadalah.id wants to show that women have the right to pursue the highest education and have a career. On the other hand, the media also provide a counter-discourse that domestic work is the responsibility of women and men.